2012
DOI: 10.1111/j.1654-1103.2012.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

Frost as a limiting factor for recruitment and establishment of early development stages in an alpine glacier foreland?

Abstract: Questions How frost resistant are the early development stages (seeds, seedlings, plantlets and juveniles) of alpine plant species? Do summer frosts impair establishment of plant species typical of different successional stages on a central alpine glacier foreland? Location Rotmoos glacier foreland, Austrian Central Alps (Obergurgl, Tyrol, Austria). Methods Seeds of 12 species typical of different successional stages were collected in the glacier foreland and either sown directly in the field or in a growth ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 55 publications
1
45
0
1
Order By: Relevance
“…The low germination of the species belonging to “Cluster A” may indicate that cold stratification is not always effective in promoting germination for alpine species or that appropriate cues for germination were not meet (Donohue, Rubio de Casas, Burghardt, Kovach, & Willis, ). The low germination of alpine species under laboratory conditions has been suggested as a mechanism to ensure the formation of a persistent soil seed bank (Mondoni et al., ; Shimono & Kudo, ), as an ecological strategy to the low chance of establishment in these environments (Erschbamer, Niederfriniger Schlag, & Winkler, ; Schwienbacher, Marcante, & Erschbamer, ), due to summer drought/heat and early autumn/spring frost episodes (Graae et al., ; Marcante, Sierra‐Almeida, Spindelböck, Erschbamer, & Neuner, ; Marcante et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The low germination of the species belonging to “Cluster A” may indicate that cold stratification is not always effective in promoting germination for alpine species or that appropriate cues for germination were not meet (Donohue, Rubio de Casas, Burghardt, Kovach, & Willis, ). The low germination of alpine species under laboratory conditions has been suggested as a mechanism to ensure the formation of a persistent soil seed bank (Mondoni et al., ; Shimono & Kudo, ), as an ecological strategy to the low chance of establishment in these environments (Erschbamer, Niederfriniger Schlag, & Winkler, ; Schwienbacher, Marcante, & Erschbamer, ), due to summer drought/heat and early autumn/spring frost episodes (Graae et al., ; Marcante, Sierra‐Almeida, Spindelböck, Erschbamer, & Neuner, ; Marcante et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…While seeds of temperate tree species are generally frost-tolerant down to -196 °C (Sakai & Larcher 1987), they lose frost hardiness with the onset of germination (Marcante et al 2012). As most temperate and boreal tree species germinate at the beginning of the growing season in spring, they are often exposed to late frost events which frequently occur in the temperate and boreal zone (Bigras et al 2004), and therefore, frost events can severely affect seedling growth and survival (Bigras et al 2004, Kreyling et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…As most temperate and boreal tree species germinate at the beginning of the growing season in spring, they are often exposed to late frost events which frequently occur in the temperate and boreal zone (Bigras et al 2004), and therefore, frost events can severely affect seedling growth and survival (Bigras et al 2004, Kreyling et al 2012. For plant species in an alpine glacier foreland, Marcante et al (2012) showed that freezing temperatures in the growing season are potentially severe enough to kill plants at early stages of their development. Similarly, Funkenberg et al (2012) demonstrated the importance of late frosts for establishment of Fallopia japonica (Houtt.)…”
Section: Introductionmentioning
confidence: 99%
“…Daneben ist in den spärlich besiedelten Gletschervorfeldflächen an sommerlichen Schön-wettertagen aber auch eine beträchtliche Erwärmung der Pflanzenorgane, der Bodenoberfläche und des Bodens zu erwarten (Neuner & Buchner 2012), sodass sogar Hitzeschäden auftreten können (Buchner & Neuner 2003 (Marcante et al 2012. Marcante et al (2012) (Marcante et al 2012). Außerdem tolerieren die vegetativen Organe der alpinen Pflanzen um 2-5 °C niedrigere Fröste im Vergleich zu den reproduktiven Teilen …”
Section: Diskussionunclassified